Comparison of the efficacy of two combined therapies for peptic ulcer bleeding: adrenaline injection plus haemoclipping versus adrenaline injection followed by bipolar electrocoagulation - Świdnicka-Siergiejko, Agnieszka; Rosołowski, Mariusz; Wróblewski, Eugeniusz; Baniukiewicz, Andrzej; Dąbrowski, Andrzej (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Introduction : Peptic ulcer remains the most frequent cause of upper gastrointestinal bleeding. Treatment of bleeding with simultaneous combination of two endoscopic techniques has proved to be more efficient than monotherapy. None of the published comparative studies of various contact coagulation modalities have confirmed the superiority of one of these techniques over the others. Aim : To compare the therapeutic outcomes of the use of a device enabling both injection of adrenaline solution and bipolar electrocoagulation (A + BE) to those of combined adrenaline injection with mechanical therapy (haemostatic clips) (A + HC) in the treatment of peptic ulcer bleeding. Material and methods : Fifty-two subjects with bleeding ulcers were assigned to the A + BE group, and 55 patients were treated with A + HC. Results: Overall, treatment failed in 20 patients (20/107, 18.7%): in 10 individuals from the A + BE group (10/52; 18.2%) and in 10 individuals from the A + HC group (10/55; 19.2%) (p > 0.05). Primary haemostasis was not obtained in 7 patients (6.5%): in 4 patients in the A + BE group and in 3 patients in the A + HC group (p > 0.05). Ten individuals (9.3%) experienced recurrent bleeding during hospitalisation: 4 patients from the A + BE group and 6 patients from the A + HC group (p > 0.05). Finally, in 96.3% of the patients (n = 103) the endoscopic treatment proved efficient with regards to obtaining haemostasis during hospitalisation. Surgical intervention was required in 4 individuals (3.7%): 2 patients in the A + BE group and 2 patients treated with A + HC (p > 0.05). Three patients (2.8%) – all from the A + HC group – died during hospitalisation. No significant intergroup differences were documented with regards to the mean number of transfused blood units and the mean length of hospital stay. Conclusions : The efficacy of combined endoscopic treatment of ulcer bleeding with a probe enabling simultaneous bipolar electrocoagulation and adrenaline injection seems comparable to the widely used dual technique of adrenaline injection and haemostatic clipping.